"The woman in green" - Neill, Roy William, 1887-1946; Rathbone, Basil, 1892-1967; Doyle, Arthur Conan, 1859-1930.; Doyle, Arthur Conan, 1859-1930.; Universal Pictures Corporation; Cinetel Films ([North Hollywood, CA] : Universal Pictures Company, Inc., 1945)
Sherlock Holmes investigates when young women around London turn up murdered, each with a finger severed off. Scotland Yard suspects a madman, but Holmes believes the killings to be part of a diabolical plot. --
Based on Sir Arthur Conan Doyle short stories 'Adventures of the empty house' and 'The final problem.'
Basil Rathbone, Nigel Bruce, Hillary Brooke, Henry Daniell, Paul Cavanaugh, Matthew Boulton, Eve Amber.
Cinematographer, Virgil Miller; editor, Edward Curtiss; musical director, Mark Levant.
In English or Spanish.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed August 21, 2015).
Keywords: Holmes, Sherlock -- Drama; Watson, John H. -- (Fictitious character) -- Drama; Moriarty, -- Professor (Fictitious character) -- Drama; Extortion -- Drama; Sherlock Holmes films; Detective and mystery films; Film adaptations; Feature films; Internet videos; Streaming video